Ni‐Metalloid (B, Si, P, As, and Te) Alloys as Water Oxidation Electrocatalysts. Issue 26 (28th May 2019) - Masa, Justus; Piontek, Stefan; Wilde, Patrick; Antoni, Hendrik; Eckhard, Till; Chen, Yen‐Ting; Muhler, Martin; Apfel, Ulf‐Peter; Schuhmann, Wolfgang
Abstract: Breakthroughs toward effective water‐splitting electrocatalysts for mass hydrogen production will necessitate material design strategies based on unexplored material chemistries. Herein, Ni‐metalloid (B, Si, P, As, Te) alloys are reported as an emergent class of highly promising electrocatalysts for the oxygen evolution reaction (OER) and insight is offered into the origin of activity enhancement on the premise of the surface electronic structure, the OER activation energy, influence of the guest metalloid elements on the lattice structure of the host metal (Ni), and surface‐oxidized metalloid oxoanions. The metalloids modify the lattice structure of Ni, causing changes in the nearest Ni–Ni interatomic distance ( d Ni–Ni ). The activation energy E a scales with d Ni–Ni indicating an apparent dependence of the OER activity on lattice properties. During the OER, surface Ni atoms are oxidized to nickel oxyhydroxide, which is the active state of the catalyst, meanwhile, the surface metalloids are oxidized to the corresponding oxoanions that affect the interfacial electrode/electrolyte properties and hence the adsorption/desorption interaction energies of the reacting species. Abstract : Compounds and alloys of nickel with the metalloids (B, Si, P, As, and Te) are emergent highly promising electrocatalysts for the oxygen evolution reaction (OER), however, the origin of their OER activity remains poorly understood. Insights into the origin of the OER activity enhancement in terms of their electronic and geometric properties and interfacial electrode–electrolyte interactions are presented.